Meningkatkan Kecerdasan Linguistik Anak Usia Dini Melalui Kegiatan Bermain Peran di RA Al-Huda : Improving Early Childhood Linguistic Intelligence through Role Play Activities at RA Al-Huda - Zarina, Nun; asrima, Nur; Pulungan, Wardah Arsidah; Putri, Azriasih; wulandari, Rantika (JURNAL TILA ( Tarbiyah Islamiyah Lil Athfaal ), 2022)
The purpose of this study was to determine the effect in depth and examine the relationship between role playing and the development of linguistic intelligence in early childhood at RA Al-Huda. This research was conducted using a descriptive method using a qualitative approach. The results of this study indicate: 1) role playing is a method that is widely used and is considered capable of developing children's linguistic intelligence because it will stimulate empathy and understand and appreciate whatever professions do other people, 2) teachers have a big role in assisting children to help shape children's character through role-playing activities, and 3) linguistic intelligence can develop better if the right methods are continuously applied. After conducting the research, the researchers concluded that role playing for early childhood can affect intelligence, especially linguistic intelligence for early childhood